Small Cell Neuroendocrine Carcinoma of Paranasal Sinuses: Radiologic Features in 14 Cases. Issue 1 (January 2021) - Lin, Naier; Qi, Meng; Wang, Zhengyue; Luo, Siqi; Pan, Yucheng; Zhang, Fang; Sha, Yan
Abstract : Purpose: The purpose of this study was to explore the characteristic computed tomography (CT) and magnetic resonance (MR) features of small cell neuroendocrine carcinoma (SNEC) of paranasal sinuses. Materials and Methods: Computed tomography (n = 8) and MR (n = 14) images and clinical findings from 14 patients with SNEC of paranasal sinuses were retrospectively reviewed. Results: Eight lesions were located in the ethmoidal sinus, 4 in the maxillary sinus, and 2 in the sphenoid sinus. Small cell neuroendocrine carcinoma of the sphenoid sinus showed bilateral asymmetry patterns. On CT images, bony changes were visible in all 8 cases. On MR, 4 cases contained hemorrhage, and 10 cases contained cystic or necrotic areas. All cases demonstrated marked heterogeneous enhancement, with half showing a "cribriform-like" or "geographic" appearance. The nasal cavity was the most common site invaded by SNEC of paranasal sinuses, followed by the orbits. A time-signal intensity curve examination showed a washout-type pattern in all but 1 case. The mean ± SD apparent diffusion coefficient value was 0.702 ± 0.112 (×10 −3 mm 2 /s). According to the Dulguerov staging system, 9 tumors were staged as N0 (1 T1, 1 T2, 5 T3, and 2 T4). The recurrence rate was 64.3%. Conclusions: Some characteristics of radiological findings can provide important clues for preoperative diagnosis.